Quantifying Agricultural Residues Biomass Resources and the Energy Potentials with Characterization of Their Nature and Ethiopian Case Consumption Inference - Angesom Gebrezgabiher Tesfay; Asfafaw Haileselassie Tesfay; Muyiwa Samuel Adaramola (Energies)
As the Ethiopian energy demand urges for fuel options, it is essential to identify biomass fuels and estimate their energy potential. This study quantified the agricultural residues’ biomass resources and their energy potential. Further analyzed and characterized the potential nature through quantitative and qualitative methodologies with descriptive, comparative, explanatory, and exploratory studies. Five-year crop yield data of 27 crops were collected from the Central Statistical Agency of Ethiopia. Conversion factors into energy were surveyed from the literature. Subsequently, the residues available and their energy potentials were estimated. Mathematical and statistical analysis methods were considered in an Excel sheet. A new measure of natural potential capacity for energy was defined in two views (resource and application). Accordingly, their potential capacities were rated and prioritized comparatively. The gross energy potential of all the residues was estimated to be 494.7 PJ. With 30% collecting efficiency, it corresponds to the imported petroleum fuel in 2018. Five major crops contributed to 80% of this gross potential. Maize and sorghum presented the highest potential due to their superior yields and good natural potential capacities. They are also well distributed in all the regions. Cotton and maize’s natural potential capacities are the best in both views. Generally, commercial crops presented better capacities than the major cereal crops. However, major crops’ energy potentials dominated due to their yields. These resources need mobilization into modern and commercially accessible fuel forms that await intervention. Densified and carbonized forms of consumption in nearby industries and households are most viable for the Ethiopian case.